Usage Pattern of Credit Card Holders - Ramalingam, P. (Indian Journal of Finance, 2009)
Indian banking institutions are having important role in the development of the economy and they provide credit facilities to the customers. The credits are broadly classified into capital and consumption credits. The capital credits are used to purchase machines and equipments. The consumption credits are needed by the customer to frequently purchase the consumption goods and services. There are various rules and regulations to get the credits. However to avoid the sufferings of the customer, the credit card system is introduced by the banking institution. The credit card business is a fast growing segment of banking in these days. The growing number of credit cards is certainly an indicator of the progress made by the Indian banking institutions. There was a time when some of the public sector banks ventured into this domain. However, there has been a dramatic change in the net of issue of credit since the banks of the new generation started popularizing the plastic card. And they have made it highly profitable too. It is reported that the income from the credit card business constitutes about eleven per cent of the pre-tax income of two of these banks in India. Public sector banks, despite their wide spread branch network and large customer base, are yet to grab the market in India.